Saving Mr. Terupt - Buyea, Rob (Delacorte Press, 2015)
"The kids from Mr. Terupt's fifth- and sixth-grade classes are entering their first year of junior high school. There's a lot to be excited about, but there are new challenges, too. Everyone is missing Mr. Terupt. When a fight threatens to break up the group forever, they think their favorite teacher is the only one who can help them. But the kids soon find out that it's Mr. Terupt who needs saving"--